Researching Catholic Education Contemporary Perspectives (Springer Singapore, 2018)
This book presents a range of perspectives on the current state of Catholic education in the opening decades of the twenty-first century. All of the chapters have their origin in an International Conference on Catholic Education, held at Heythrop College (University of London) in September 2016. The book brings together many leading scholars to present a survey of the latest research on Catholic education in areas such as the aims of Catholic education, Catholic schools and Catholic identity, leadership issues in Catholic schools and fresh thinking about the place of Religious Education (RE) in Catholic Education. This book demonstrates how the field of Catholic Education Studies has firmly come of age. Rather than being a subfield of educational or theological discourse, it is now an established field of research and study. As such, the book invites readers to engage with much of the new thinking on Catholic education that has grown rapidly in recent years. It offers a broad range of contemporary perspectives on research in Catholic Education and rich insights into current thinking about Catholic Education.